Museum Landscape Transformation: Suitability Assessment Analysis and Design Model Development - Agustinus Denny; Liyushiana Liyushiana; Ananda Pratiwi Panjaitan; Joy Ferry Ando Sinaga; Septi Anggina Sitinjak (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2024)
Museums play a pivotal role in the tourism industry, offering cultural and educational experiences to visitors. To remain competitive, museums must develop distinctive landscape and facility designs that enhance their appeal as tourist destinations. This research focuses on Rahmat International Wildlife Museum and Gallery, a private museum in Indonesia, aiming to improve its landscape and facility design to create a more captivating visitor experience. Using Minister of Tourism and Creative Economy Regulation No. 4 of 2021 as a benchmark, the study evaluates Rahmat Museum's compliance with business standards for private museums. The research adopts a qualitative approach, including in-depth interviews, direct observations, and a literature review. Findings indicate that the museum excels in visitor convenience, hygiene, and engagement but requires improvements in waste management, community involvement, and physical accessibility. To enhance Rahmat Museum's landscape and facility design, the study proposes three key enhancements: an accessibility ramp, an accessible toilet, and separate waste storage. These recommendations aim to ensure inclusivity, convenience, and environmental sustainability. Implementing these proposals is expected to address non-compliance issues and elevate Rahmat International Wildlife Museum and Gallery's status as a premier tourist destination. This research offers valuable insights for other private museums seeking to enhance their landscape and facility designs to attract visitors and ensure business sustainability